2011
DOI: 10.4236/ce.2011.23042
|View full text |Cite
|
Sign up to set email alerts
|

Quality Issues in Higher Education: A Multicriteria Framework of Satisfaction Measures

Abstract: Higher education attributes significant interest to student satisfaction because of its potential impact on the quality dimensions of the offered services. This is illustrated from the large number of studies that have shown a moderate to strong relationship between these two concepts. This paper provides a detailed analysis of a student satisfaction survey conducted at the Health Care Management Department of the Technological Education Institute of Athens. The analysis was based on a multi-criteria preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Based on the literature review that proves that private universities have a better potential to satisfy students (El Gamal and Abd El Aziz, 2011b); especially in countries with very high population such as Egypt (Abd El Aziz, 2009), and due to the variety of findings regarding the main criteria that affect student satisfaction in different contexts (Butt and Rehman, 2010) (Huang et al, 2011) (Dimas et al, 2011) (Gruber et al, 2010) (Khodayari andKhodayari, 2011)(Oscar et al, 2005) (Archambault, 2008) (Kelso, 2008) (Hanover, 2010)it was worth testing whether students are satisfied with the current educational services provided at private universities in Egypt . Accordingly, a number of hypotheses have been devised and the research framework as shown in figure 1 was developed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the literature review that proves that private universities have a better potential to satisfy students (El Gamal and Abd El Aziz, 2011b); especially in countries with very high population such as Egypt (Abd El Aziz, 2009), and due to the variety of findings regarding the main criteria that affect student satisfaction in different contexts (Butt and Rehman, 2010) (Huang et al, 2011) (Dimas et al, 2011) (Gruber et al, 2010) (Khodayari andKhodayari, 2011)(Oscar et al, 2005) (Archambault, 2008) (Kelso, 2008) (Hanover, 2010)it was worth testing whether students are satisfied with the current educational services provided at private universities in Egypt . Accordingly, a number of hypotheses have been devised and the research framework as shown in figure 1 was developed.…”
Section: Methodsmentioning
confidence: 99%
“…The questionnaire included two tested factors scattered among 5Likert scale questions, with the following coding 1 for 'totally agree', 2 for 'agree', 3 for 'neutral', 4 for 'disagree', and 5 for 'totally disagree'. Questionnaire questions were adopted and adapted from literature review (Butt and Rehman, 2010) (Huang et al, 2011) (Dimas et al, 2011) (Gruber et al, 2010).…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in USA found that faculty, academic staff, and classes are the main criteria that affect students' satisfaction [11]. Another study also conducted in USA revealed that there are significant relationships between service performance and student satisfaction that will aid institutions to predict and measure student satisfaction and retention [12].In Pakistan, a study revealed that teachers' expertise, courses offered, learning environment and classroom facilities are the main criteria that affect the student satisfaction with the quality of education offered by different private and public sector universities [13]. A study conducted in Athens, Greece identified five different criteria as the criteria for students' satisfaction; namely program study, academic staff, equipment, administrative services, and image [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous scientific analyses and studies deal with methods and sequences which can find these differences, express them or specify them exactly. However, this type of research is focused on chosen groups of products, activities or services with the same or similar characteristics (eg, Bigne, Moliner & Sanchez, ; Dimas, Goula & Pierrakos, ; Ehlers & Hilera, ; Sallis, ; Shrikanthan & Dalrymple, ).…”
Section: Evaluation Of the Quality Of Educational Resourcesmentioning
confidence: 99%